Hand reanimation: functional free gracilis transfer or transfer of the distal tendon of the biceps to the flexor digitorum profundus and flexor pollicis longus as surgical options - Raquel Bernardelli Iamaguchi; Maria Virginia Arranz; Rames Mattar Junior (Einstein (São Paulo))
ABSTRACT Objective: Hand reanimation for finger flexion in patients with total paralysis remains a reconstructive challenge, especially when tendon transfers or neurological reconstruction options are no longer viable. This study aimed to describe a series of patients without hand function by evaluating two hand reanimation techniques. Methods: This observational retrospective study used a case series of hand reanimation. Two techniques were performed-functional free gracilis muscle transfer with microsurgical reconstruction, and transfer of the recovered biceps to the flexor digitorum profundus and flexor pollicis longus with tendon graft augmentation. The two groups, each undergoing one of the techniques, were evaluated for the final functional results using the British Medical Research Council (BMRC) grading system. Results: Six consecutive patients with total hand paralysis were included, with a mean final follow-up of 7.5 years. After intervention, two patients, one from each technique group, achieved a BMRC grade 2. In the group where tendon transfer of the biceps to the finger flexors was performed, two patients achieved a BMRC grade 3. Additionally, two patients who underwent functional free muscle transfer were achieved a BMRC grade 4. Conclusion: The transfer of biceps to the finger flexors using tendon grafts, which involves fewer technical difficulties and reduced demands from the surgical team compared to functional free muscle transfer, is a viable alternative for treating patients requiring hand reanimation. However, functional free muscle transfer is recommended as the first option when technically feasible and adequate donor nerves are available, due to its potential for achieving greater final muscular strength in the finger flexors. Reconstructive microsurgeons can use both techniques as viable surgical options for hand reanimation.